The Knowledge, Behaviour, Attitudes and Perception of Young Nigerian Adults towards HIV/AIDS and its Prevention: A Systematic Review - Orukwowu, Udo; George, Boma Iweriso; Ene-Peter , Janet (IPS Journal of Basic and Clinical Medicine, 2022)
This piece of work is a systematic review that critically appraises past research studies, not later than five years that is directed towards investigating the knowledge, awareness, behaviour, attitudes and perception of young people in Nigeria towards HIV/AIDS and its prevention. Young people’s knowledge, awareness and perceptions have been identified in different levels and categories. Young people’s preventive awareness level and risk perceptions have also been revealed. Conclusively, the findings from the different studies selected for the systematic review have shown varying degrees of HIV knowledge among young people. This is to address the perceptions of young Nigerian adults towards HIV/AIDS. Significantly, the systematic review undertaken confirms the original theme of the study identifying and exploring the knowledge, attitudes, behaviours and perceptions of young adults to address the aim of the study. The results have, therefore, indicated that those in the colleges and universities were more knowledgeable than those that were not. Understanding of the virus helped to influence young people in their attitude towards infected people. Furthermore, understanding of HIV/AIDS and its prevention also differed among young adults; those in the university had better understanding compared to those in the colleges and dropouts.